Double Emulsions as Potential Fat Replacers with Gallic Acid and Quercetin Nanoemulsions in the Aqueous Phases - Silva-Weiss, A; Silva-Vera, W; Gimenez-Castillo, B (Elsevier Ltd, 2018)
The development of fat replacers to obtain healthier/functional foods is a constant challenge. With this aim, double emulsions (DE) with a blend of olive, linseed and fish oils as oil phase were developed. To prevent the oxidation of these oils, gallic acid and quercetin were incorporated in the internal and the external aqueous phase (W2), respectively, according to a factorial design. Considering the low solubility of quercetin in water, it was included in O/W nanoemulsions (QN), thus being freely dispersible in W2. The antioxidant activity in DE was attributed to QN, which significantly improved the oxidative stability of DE/QN. Furthermore, DE/QN showed good physical stability with a limited coalescence during storage at 4 °C for 28 days, significantly longer than time usually required for food ingredients. Therefore, DE/QN could be used as potential fat replacer in a variety of food formulations, providing blends of fatty acids consistent with dietary recommendations. © 2018 Elsevier Ltd